Life Cycle Assessment of Energy Retrofit Measures in Existing Healthcare Facility Buildings: The case of Developing Countries - Mabdeh, Shouib; Ali, Hikmat; Al-Momani, Magd (International Journal of Energy Economics and Policy, 2022)
Although retrofitting existing buildings is an important step toward sustainability, most research have concentrated on the sustainability of new structures. Existing buildings retrofit is being questioned, particularly in terms of selecting the optimal solution. Additionally, thermal comfort is crucial for patient satisfaction in healthcare facilities, but enhancing this factor increases energy use. However, envelope retrofitting of healthcare facilities buildings stock provides a high potential for energy savings. Consequently, this study aims to develop envelope retrofitting guidelines for uninsulated healthcare buildings in Jordan and to propose locally available retrofit measures. The difference in the building performance before and after retrofit is used to assess potential energy savings. Next, this outcome is used in a life cycle assessment (LCA) to examine the economic and environmental feasibility of the proposed retrofit measures using life cycle cost and life cycle CO2. This procedure combines the best economic and environmental measures available to create a comprehensive retrofit strategy. Thus, this study adopts a mixed-method design combining quantitative and qualitative methods, including physical analysis, national archives, and questionnaires. The results show that all proposed measures are economically and environmentally feasible, and the combination of two or more measures could produce up to 33% energy savings. Finally, the holistic approach strategy is investigated with various healthcare facilities’ life cycle.